Application of Group Positive Psychotherapy(GPPT) to Increasing Well Being in Women with Systemic Lupus Erithematosus (SLE) - Auliya Ulil Irsyadiyah; Ahmad Gimmy Prathama Siswadi; Nurul Wardhani (Universitas Katolik Soegijapranata, 2019)
Systemic Lupus Erithematosus (SLE) is a chronic autoimmune disorder that can affect almost all organs of the body. SLE is part of the chronic illness disabilities (CID) with the highest number of women reproductive age. Not only the physical affects but also quite disturbing psychological conditions, for example increased negative emotions, depression, and suicidal ideation. Chronic illness disabilities (CID) patients often have low perception of life satisfaction and will affect a person's level of well-being. To achieve the condition of well-being, psychological interventions that can help increase the level of well-being in women with Systemic Lupus Erithematosus are needed. The intervention was a group positive psychotherapy by pleasent life, engaged life and meaning full life. The purpose of this research can help individuals to improve well-being especially for women with Systemic Lupus Erithematosus. In this research, Group Positive Psychotherapy was conducted in 14 sessions with pre-test and post-test. This research is a case study with a single case experimental design. The method used is mixed method with concurrent embedded strategy, using qualitative data as primary and quantitative data as secondary data. The measuring instrument used is The PERMA Profiler with a reliability value of 0,761 compared to Cronbach’s Alpha which is r0,6 reliable. The participants in this study were 3 people. Based on qualitative results indicate that there is an increase in the level of wellbeing in the 3 participants and increasing score in 5 aspects of well-being after intervention.